2017
DOI: 10.1089/scd.2016.0289
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Heat Shock Proteins Enhances the Stemness of Frozen–Thawed Adipose Tissue-Derived Stem Cells

Abstract: Extensive research has been performed to determine the effect of freezing protocol and cryopreservation agents on the viability of adipose tissue-derived stromal/stem cells (ASCs) as well as other cells. Unfortunately, the conclusion one may draw after decades of research utilizing fundamentally similar cryopreservation techniques is that a barrier exists, which precludes full recovery. We hypothesize that agents capable of inducing a subset of heat shock proteins (HSPs) and chaperones will reduce the intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…For control samples, stromal media containing DMEM with 10% FBS and 1% antibiotic was used. After 10 days, the adipogenic differentiated cultures were fixed in 4% paraformaldehyde and stained using the Oil Red O stain as described in several previous studies 17 , 19 , 21 , 22 . Quantitation of adipogenic staining was carried out by eluting the Oil Red O stain by 100% isopropanol followed by measuring absorbance of the elution at 510 nm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For control samples, stromal media containing DMEM with 10% FBS and 1% antibiotic was used. After 10 days, the adipogenic differentiated cultures were fixed in 4% paraformaldehyde and stained using the Oil Red O stain as described in several previous studies 17 , 19 , 21 , 22 . Quantitation of adipogenic staining was carried out by eluting the Oil Red O stain by 100% isopropanol followed by measuring absorbance of the elution at 510 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, ASCs cryopreserved with DMSO and PVP and stored for 2 weeks at −196 °C maintained their osteogenic and adipogenic potentials as well as their post thaw viability 21 , 39 . We have recently reported that thermally pre-conditioned ASCs cryopreserved in either DMSO or PVP and stored for 1 day at −196 °C displayed enhanced cell viability while retaining their differentiation plasticity 22 . Cryopreservation of human ASCs for 3 months in liquid nitrogen displayed no sign of deterioration in their functionality regarding immunophenotype, differentiation potential, proliferation, and viability 67 .…”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Oil Red O staining, the samples were fixed in a 4% paraformaldehyde solution for 10 min, washed with PBS and stained with 0.3% w/v% Oil Red O solution (in 60% isopropanol) for 8 min, followed by washing with 60% isopropanol for 30 s. Bright field images were taken by microscope (IX73, Olympus, USA). The samples were then de‐stained with 100% isopropanol for 5 min to extract the Oil Red O according to the previous study . Absorbance of the de‐staining solution was measured at 510 nm wavelength using a plate reader (SpectraMax M5, Molecular Devices LLC, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The PBS solution were warmed to 37 o C and the washing steps were repeated four times. Detailed cell isolation and culture processing procedures are available elsewhere [7,40]. After isolation, the cells were centrifuged at 300g for 5 min.…”
Section: Methodsmentioning
confidence: 99%